2022
DOI: 10.1080/19768354.2022.2049640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of black garlic on the pacemaker potentials of interstitial cells of Cajal in murine small intestine in vitro and on gastrointestinal motility in vivo

Abstract: Black garlic (BG) is a newly explored food stuff obtained via fermentation of raw, healthy garlic, especially in Asian countries. Interstitial cells of Cajal (ICC) are the pacemaker cells of gastrointestinal (GI) motility. The purpose of this study was to investigate the effects of BG extract on the pacemaker potentials of the ICC in the small intestines of mice and the possibility of controlling GI motility. The antioxidant activity of BG extract was also investigated. The whole-cell electrophysiological meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As pacemakers, ICCs are crucial for GI motility and are involved in neurotransmission [4][5][6][7][8]. Recent breakthroughs have been made in understanding the ICC activation mechanism, including the diversification of research methods [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As pacemakers, ICCs are crucial for GI motility and are involved in neurotransmission [4][5][6][7][8]. Recent breakthroughs have been made in understanding the ICC activation mechanism, including the diversification of research methods [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, slow waves cannot be explained by the relationship between GI smooth muscles and motor nerves alone [2]. Instead, interstitial cells of Cajal (ICCs) appear to be the primary cause of slow waves [4][5][6]. In recent decades, intensive research in animal models (e.g., mice, guinea pigs, and dogs) has revealed that ICCs act as pacemakers in the stomach, small intestine, and large intestine [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Caco-2BBE cells were washed with sterile phosphate-buffered saline and treated with RIPA buffer containing proteinase inhibitors (Sigma-Aldrich, St. Louis, MO, USA). Cell lysates were prepared and subjected to western blotting as previously described (Moon et al 2022 ; Um et al 2023 ) using antibodies against ChREBP (NB400-13; Novus Biologicals, Centennial, CO, USA), GLUT5 (27571-1-AP; Proteintech, Rosemont, IL, USA), GAPDH (MAB374; Millipore, St. Louis, MO, USA), and TATA-binding protein (TBP) (ab63766; Abcam, Cambridge, UK). To detect nuclear ChREBP, nuclear lysates of Caco-2BBE cells were obtained using the NE-PER™ Nuclear and Cytoplasmic Extraction Reagents Kit (78833; Thermo Fisher Scientific, Carlsbad, CA, USA), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the SGR extract appeared to be safe and did not elicit acute toxicity for a single oral dose of at least 5 g/kg or below. In this paper, SGR 0.01 g/kg, 0.1 g/kg, and 1 g/kg were used in the animal experiment, and this concentration has been widely used in the mouse gastrointestinal animal experiments [ 33 , 37 , 40 , 41 , 42 , 48 , 49 , 50 , 51 ]. When converted to human concentration, 1 g/kg for a mouse is 4.9 g for adults (60 kg) [ 52 ], which is less than the typical human dose of 15–60 g [ 23 ].…”
Section: Methodsmentioning
confidence: 99%